Gambaran Kesehatan Mental Pada Tenaga Kesehatan Kantor Kesehatan Pelabuhan Di Masa Pandemi Coronavirus Disease-19 (COVID-19) Tahun 2021 - Ginanjar, Sutan Harya; Udijono, Ari; Kusariana, Nissa; Sutiningsih, Dwi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
The increase of COVID-19 cases in Indonesia is in line with the increasing duties of health workers at the point of entry of the country. The task of handling COVID-19 provides psychological pressure and potential to cause depression, stress, and anxiety problems for health workers. This type of research was analytic observational with a cross-sectional design. Data collection was collected by online survey on May to August 2021. The Number of sample in this study was 350 health workers at Health Quarantine Offices in Indonesia. The mental health data collection instrument used DASS-21 questionnaire to check the level of depression, stress, and anxiety. The result showed that there was health workers with moderate to very severe depression in Health Quarantine Offices were 104 respondents (29,7%). The level of anxiety of health workers with moderate to very severe category was 146 respondents (41.7%). Meanwhile, the stress level of health workers with moderate to very severe category was 79 respondents (22,6%). The researcher concludes that the identification of data about the level of depression, anxiety, and stress in health workers at the Quarantine Health Office was needed as an effort to prevent of mental health disorders in health workers. Joint collaborative actions can be pursued by various parties, especially in providing interventions to deal with mental health problems for health workers during the COVID-19 pandemic.